Jade green : a ghost story - Naylor, Phyllis Reynolds (Scholastic, Inc., 2007)
While living with her uncle in a house haunted by the ghost of a young woman, recently orphaned Judith Sparrow wonders if her one small transgression causes mysterious happenings.